IMPLEMENTASI MODEL GI-GI (GROUP INVESTIGATION-GUIDED INQUIRY) PADA PEMBELAJARAN GERAK MELINGKAR DI SMA - Swit Tanti Rahayu Ningsih; Indrawati Indrawati; Yushardi Yushardi (JURNAL PEMBELAJARAN FISIKA, 2017)
This research aimed to study the effect of GI-GI model on students scienceprocess skills and students multirepresentation ability of circular motion concept.This type of research was experimental research by post-test only control design.This research was conducted in SMAN 1 Jenggawah. Population in this study werestudents of class X at SMAN 1 Jenggawah of Academic Year 2016/2017. Sampleswere taken with cluster random sampling, X IPA 1 as an experiment class and X IPA2 a control class. The techniques of data collection were observation, interviews,documentation and testing. The technique of data analysis used independent samplet-test. The results of this analysis were obtained significance value of 0,000 forscience process skills of student and 0,000 for multiple representation ability ofstudent. It can be concluded that model of GI-GI give significantly effect on studentsscience process skills and students multirepresentation ability in learning circularmotion at SMAN 1 Jenggawah.Key words: circular motion, GI-GI model, multirepresentation ability, scienceprocess skills